The Influence between Salary Satisfaction, Job Satisfaction, Affective Commitment, Performance, and the Desire to Change - Agung Pambudi Nugroho; Justine Tanuwijaya (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The purpose of this study was to determine the effect of salary satisfaction, job satisfaction, affective commitment, performance, and the desire to change jobs on employees of the food and beverage industry. Measurements were carried out using a questionnaire to 125 respondents of food and beverage industry employees who had worked for more than 1 year using the structural equation modeling (SEM) method and questionnaires as the main data. The results showed that salary satisfaction had a significant effect on job satisfaction. Salary satisfaction and job satisfaction have a significant positive effect on employees' affective commitment. Job satisfaction has a significant effect on performance, affective commitment and performance have a significant effect on the desire to change jobs, but salary satisfaction and job satisfaction show no significant effect on employee turnover intentions. This finding has implications for top management of human resources in the food and beverage industry in determining strategies to achieve company goals.